(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Preschool education marks the foundational years of a child’s cognitive and social development. Among the myriad of skills that are cultivated during this crucial period, speech and language development play a pivotal role in shaping a child’s future academic success and overall well-being. This article delves into the importance of speech correction exercises in preschool education, examining how targeted interventions can positively impact a child’s linguistic abilities, social interactions, and future academic achievements.